(untitled) (Baltic Journal of Sport and Health Sciences, 2019)
Background. Simultaneously manifested collaboration and competition capabilities are coordinated. This harmony is determined by social interdependency of participants of the activity. It is also true about the dancesport activity. Dancesport dancers mostly compete for higher results, but collaboration is obligatory in order to achieve that result. The problem question was what the educational presumptions of the coordination of collaboration and competition in the dancesport activity are. The research aim was to create the conceptual model of the educational presumptions of the coordination of collaboration and competition in the dancesport activity. Research method was theoretical analysis and synthesis. The results of theoretical analysis are generalized and incorporated into the conceptual model. Discussion and conclusions. The theoretical model of the educational presumptions of the coordination of collaboration and competition in dancesport compiled and presented on the basis of the analysis of scientific literature reveals the conceptual basis of the educational presumptions of the coordination of collaboration and competition in dancesport. Dancesport dancers act and strive for sport and personal goals by using collaboration and competition capabilities, coordinating them and reaching the higher form of coopetition (harmony). The model of the educational presumptions of the coordination of collaboration and competition in dancesport is based on the analysis of literature about the forms of the interpersonal interaction both in the social environment and sport activity, manifestation of discussed forms of the interaction and theory of empiric learning including capabilities.